Study the Possible Effect of Inula Graveolens L. Methanolic Extract on Antioxidant Status i n Track and Field Male Athletes - lMAD FARAJ BADRAWl (University of Basrah, 2024)
The antioxidant activity of Inula graveolens L. methanolic extract could be attributed to its higher content of both phenolic and flavonoid compounds. Therefore, the present study was undertaken to assessment the possible effect of methanolic extract of Inula graveolens L. plant as an improvement of enzymatic and non-enzymatic antioxidant status in track and field male athletes. Levels of enzymatic, non-enzymatic antioxidants and other general biomarkers were determined in serum and urine before (D0) and after (D30) supplementation of 400 mg of MEIG or placebo once at day for 30 day in elite group. This study showed increased significantly (P < 0.01) in the levels of vitamines A, E and C with compared to placebo group. On the other hand, no significant variation was seen in the levels of CAT, GRx, and SOD activities was disclosed; whereas, such was not the case as regards glutathione peroxidase (GPx). This enzyme activity decreased during the placebo period (p < 0.05) while remaining unaltered throughout the MEIG intake period. Same table reflect that the CK activity reached 686 ± 1.5 and 470 ± 1.4 (U/L) after placebo and MEIG periods, respectively (P < 0.01). Furthermore, data obtained, was shown that during placebo supplementation, urinary excretion of isoprostanes was markedly increased, disclosing thereby, an increase in oxidative injury and inflammation (1.29 ± 0.11 vs 1.75 ± 0.18 ng/mg creatinine at D0 and D30, respectively; p < 0.05). Such an increase did not appear during the MEIG supplementation (1.35 ± 0.12 vs 1.37 ± 0.13 ng/mg at D0 and D30, respectively). Finally, no significant difference on cholesterol and triglycerides was evidenced whatever the period (placebo or MEIG). Regardless of the capsule content the athletes had, no modification of urea concentration was observed; whereas, ferritin concentration was significantly reduced in both cases. Also, Hb concentration was not modified in the placebo group; however, MEIG supplementation increased Hb concentration, as opposed to placebo intake, respectively (12.8 ± 0.3 vs 12.6 ± 0.2 g/dL, p < 0.05).